PENGARUH BUDAYA PATRIARKI TERHADAP KESETARAAN GENDER DALAM KELUARGA HINDU BALI - Widhiyana, Made (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
The study of the influence of patriarchal culture on gender equality in Hindu families focuses on the position of women due to the implementation of patriarchal culture to date. The purpose of writing this article is to understand the life of Hindu society which adheres to a patrilineal system and is influenced by patriarchal culture towards gender equality in ancient times before Science and Tecnology (IPTEK) developed and today’s increasingly advanced times. The method used is empirical or sociological and uses a literature study approach. The data obtained either through direct observation or from related literature is processed in a qualitative deckriptive manner. Various phenomena that occur in the field due to the influence of patriarchal culture show that women tend to be the ones who suffer losse. Because in term of position, women are below men. Apart from that, women’s space for movement ia also limited, as if a woman’s job is only to serve her husband and take care of the household and children. It is hoped that this research can contribute to the understanding that the implementation of patriarchal culture actually needs to be adjusted to current developments in family life. From the research carried out, the results obtained were that Hindu families who still implement patriarchal culture tend to have a bad impact. The various violence that befalls women in Hindu families, such as physical, psychological and sexual violence, cannot be separated from the negative influence of patriarchal culture. Moreover, Hindu families adhere to the patrilineal system.